Pencapaian HOTS (Higher Order Thinking Skills) Mahasiswa Program Studi Pendidikan Fisika FKIP Universitas Samawa - Muhammad Erfan; Tursina Ratu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
Higher Order Thinking Skills (HOTS) are essential skills for prospective teachers in the 21stÃÂ  century. HOTS in the cognitive domain includes the ability in analyzing (C4), evaluating (C5), and creating (C6). In the process of mastering HOTS, one must know first what level of thinking skills he/she has. Therefore, this study aims to measure the achievement of the cognitive thinking skills of students of the Physics Education Study Program, Faculty of Teacher Training and Education University of Samawa. The measurement used test instrument in the form of essay test, then the results of the thinking skills achievement for each cognitive domain of students divided into three categories (low, medium and high). The result ofÃÂ  the studentÃ¢â¬â¢s achievement of the cognitive thinking skillsÃÂ  obtained by students were in low category of 55%, the medium category of 11%, and 34% in the high category for mastering lower-order thinking skills (LOTS), while for HOTS, 100% was in low category and it can be concluded that the achievement of students' cognitive thinking skills is still in lower-order thinking skills.